Existence and uniqueness of almost periodic solutions for a class of nonlinear Duffing system with time-varying delays - Yanli Xu (Electronic Journal of Qualitative Theory of Differential Equations, 2012)
In this paper, we investigate the existence and uniqueness of almost periodic solutions for a class of nonlinear Duffing system with time-varying delays. By using theory of exponential dichotomies and contraction mapping principle, we establish some new results and give an example to illustrate the theoretical analysis in this work.